Expressing stacked HRAP and PFLP genes in transgenic banana has no synergistic effect on resistance to Xanthomonas wilt disease - Muwonge, A.; Tripathi, J.N.; Kunert, Karl J.; Tripathi, L. (Elsevier, 2016)
Banana production in Africa's great lakes region is threatened by the Banana Xanthomonas wilt (BXW) disease caused by Xanthomonas campestris pv. musacearum, a biotrophic pathogen. Transgenic banana plants, cv. “Gonja manjaya,” expressing stacked hypersensitive response-assisting protein gene (HRAP) and the plant ferredoxin-like protein gene (PFLP) were evaluated for resistance against BXW in comparison to transgenic lines having single gene. Transgenic lines with stacked gene as well as single gene had higher resistance to the pathogen than non-transgenic control plants indicated by either no symptom development or delayed symptoms for completely and partially resistant plants, respectively. Transgenic lines also produced more hydrogen peroxide due to pathogen infection and also had higher transcription of stress response genes encoding NPR1, a defense response co-transcriptor, the antimicrobial PR-3 and glutathione S-transferase. However, transcription of PR-1, an indicator for infection with a biotrophic pathogen, was not increased in both stacked and single transgenic lines, indicating a possible shift to infection with a necrotrophic pathogen in plants due to transgenes expression. Expression of stacked HRAP and PFLP genes in transgenic banana lines did not show higher or additive resistance levels against pathogen in comparison to individual genes; however, stacking might provide the benefit of durable resistance in case one transgene function is lost.